PENGARUH SUMBER TANNIN TERHADAP KADAR PROTEIN DAN DAYA SIMPAN TELUR PINDANG - Eka Astari Hakim; Mars Khendra Kusfriyadi; Agnescia Clarissa Sera (JURNAL RISET GIZI, 2019)
Backgroung : Pindang eggs are traditional egg-processed products using tanneries that will denaturing the egg proteins. Guava leaves, tea pulps, shallot skin and onion skin are comionly used for making pindang eggs as they contain tannin.Objective : This study aimed to analyze the effect of tannin sources on protein content and shelf life of pindang eggs.Method : This study used an experimental method with a Completely Randomized Design (CRD) design to examine the difference between tannin using guava leaves, shallot skin, tea pulp, bombay onion skin with 6 times of repetition. Protein content on pindang eggs processed with onion, guava leaves, tea pulp, and onion skins were 13,0%, 12,95%, 12,90%, and 12,80% respectively.Result : There was a significant effect of the addition of tannin sources on the levels of pindang egg protein (p = 0.000, α = 5%). Pindang  eggs have an average shelf life of 20 days. On the 30th day, almost all of pindang eggs with 4 types of tanneries has deteriorated  while the microbiological tests of  all pindang eggs on the 20th day of bacteria have exceeded SNI requirements. There is a real effect of the decay of each tannin source on the storage time of pindang eggs (p = 0.000, α = 5%). There is an influence from the tannin sources from guava leaver, tea pulp, shallot skin, onion skin on egg protein content. The best treatment was found in shallots with a percentage of protein content reached 13.00%.Conclusion : There is an influence from the source of tannin, guava leaves, tea pulp, shallot skin, onion skin to the durability of pindang eggs. The best treatment for 30 days is found in tea grounds and onion skin while in microbial studies all pindang eggs have exceeded SNI requirements